Economic Cycle and the Large-Scale Asset Allocation Strategy of Chinese National Social Security Fund - Tang, Zijie (Asian Economic and Financial Review, 2020)
Based on the quarterly data of GDP from 1993 to 2018, this paper forecasts that China is in a recession period at present, and the trend of economic cycle in the next ten years is divided into five stages, which can be approximately regarded as a sequential evolution of Juglar-cycle. Combined with the prediction results, the BL model is used to allocate the assets of the three parts of the social security fund: stock, debt and cash. The results show that: 1) when only considering cash, stock and bond, the impact of economic cycle on the allocation of large categories of social security fund assets is not severe, but it has a significant impact on the style and industry rotation of large categories of assets; 2) according to the calculation of the model, the cash assets of social security fund are deposited. In case of over matching, it should be adjusted to the level near the minimum limit of 10%.